Development of an HPLC method for formic acid analysis through peak exclusion approach - Hasan, Daniyal; Mahmood, Iram; Ahmad, Ishfaq; Aziz, Farah; Ahmad, Ishaq (Penerbit Universiti Kebangsaan Malaysia, 2019)
High Performance Liquid Chromatography (HPLC) is a chemical analysis technique that gives both the quantitative and qualitative analysis of liquid samples. A certain set of parameters, called HPLC method, are defined for analysis of every discrete mixture. Often literature is not available or specifically reported expensive HPLC apparatus is not available for every set of mixtures. Present study concentrated on analysis of formic acid from a mixture of methanol, formaldehyde and water. Formic acid is a basic carboxylic acid that has growing industrial and commercial uses, especially as a refrigerant. A C-18 column was utilized for the analysis by optimizing the parameters like dimensions of the stationary column, nature of mobile phase, flow rate of mobile phase and wavelength of the ultraviolet detector. Comprehendible and reproducible results for the analysis of formic acid were obtained on 25 cm long C-18 stationary column, by tuning the combined effect of water as mobile phase at a flow rate of 1 mL/min and by excluding the unnecessary peaks at 250 nm wavelength of ultraviolet detector, called peak exclusion approach. The calibration curve was found to be linear over the range of 1.25 % v/v formic acid solution in methanol up to 100 % pure formic acid. Limit of detection (LOD) and limit of quantitation (LOQ) were found to be 2.25 % and 6.83 %, respectively.